2018
DOI: 10.1111/1462-2920.14289
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi stimulate organic phosphate mobilization associated with changing bacterial community structure under field conditions

Abstract: The extraradical hyphae of arbuscular mycorrhizal fungi (AMF) harbour and interact with a microbial community performing multiple functions. However, how the AMF-microbiome interaction influences the phosphorus (P) acquisition efficiency of the mycorrhizal pathway is unclear. Here we investigated whether AMF and their hyphal microbiome play a role in promoting organic phosphorus (P) mineralizing under field conditions. We developed an AMF hyphae in-growth core system for the field using PVC tubes sealed with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 54 publications
6
72
1
Order By: Relevance
“…The collected soil was air dried and sieved (2 mm). The basal nutrients were added to the soil as described in recruited a hyphosphere microbiome that has the potential to stimulate the solubility of organic P [6,7]. In this study, to enhance the colonization of soil microbiome in hyphosphere, 100 mg kg -1 myo-inositol hexaphosphate calcium magnesium salt (phytin, TCI, Tokyo, Japan) (equaling to 20 mg P kg -1 soil) was added to the hyphal compartment as an organic P resource.…”
Section: Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…The collected soil was air dried and sieved (2 mm). The basal nutrients were added to the soil as described in recruited a hyphosphere microbiome that has the potential to stimulate the solubility of organic P [6,7]. In this study, to enhance the colonization of soil microbiome in hyphosphere, 100 mg kg -1 myo-inositol hexaphosphate calcium magnesium salt (phytin, TCI, Tokyo, Japan) (equaling to 20 mg P kg -1 soil) was added to the hyphal compartment as an organic P resource.…”
Section: Soilmentioning
confidence: 99%
“…3, 4, 5 and 6). All these results suggested the microbiomes that associated with the three AM fungal species were distinct.Previous studies have indicated that the hyphosphere microbiome are directly involved in soil organic N, P, C mineralization[7,27,31,34,35]. For example,Pseudomonas and Bacillus are reported to have abilities to mobilize sparingly soluble P in soil(Table S5)[5,7].…”
mentioning
confidence: 99%
“…Importantly, the relationship between AMF and bacteria in P utilization can be regulated by the C:P ratio in soil [44] ; reducing soil C:P ratio by adding starter P fertilizer to Pdeficient soils can stimulate the P-solubilizing capacity of bacteria and improve plant P uptake [45] . AMF hyphae recruit bacteria that produce alkaline phosphatase and perform the functions, which are absent in fungal hyphae, to enhance soil organic P mineralization in situ in the field [44,46] . Also, a recent study showed that the stimulating effect of AMF on hyphosphere bacteria can be influenced by various abiotic and biotic factors.…”
Section: Phosphorus In the Mycorrhizospherementioning
confidence: 99%
“…Fungal hyphae provide a unique niche for bacterial colonization, in which bacteria benefit from their fungal partner by obtaining suitable carbon or energy sources from fungal exudates (1,2). In return the specific bacterial communities recruited by fungal hyphae may help the host fungi by accessing recalcitrant forms of soil nutrients and hence meet the host's nutrient requirements (3).…”
Section: Introductionmentioning
confidence: 99%